2013
DOI: 10.5114/jcb.2013.34340
|View full text |Cite
|
Sign up to set email alerts
|

Individual applicator for brachytherapy for various sites of superficial malignant lesions

Abstract: The aim of this paper is to discuss brachytherapy treatment and individual applicators suitable for unfavorably localized superficial malignant lesions. Techniques for manufacturing an individual applicator and clinical examples of its use for various locations of cancer are presented. This techniques are based on individual size and shape of the tumour. CT-planning make the technique adequate for individual patient history and type of tumour. Featured techniques seems to be very useful and easy to performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…In fact, during HDR-BT, the dose remains on the surface and does not penetrate deeply with optimal sparing of normal tissues due to dose concentration into the clinical target volumes (CTV) and rapid dose fall-off at target periphery [10, 11, 12, 13, 14, 15, 16, 17]. Published studies have mainly reported standard fractionation and hypofractionated brachytherapy regimens in patients treated with HDR-BT, and the biological effective dose (BED) was often calculated due to define the total dose and dose for fractions regimen for a better local control and acceptable late and acute toxicity [19, 20, 21, 22, 23, 24, 25, 26, 33, 34, 35, 36, 37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, during HDR-BT, the dose remains on the surface and does not penetrate deeply with optimal sparing of normal tissues due to dose concentration into the clinical target volumes (CTV) and rapid dose fall-off at target periphery [10, 11, 12, 13, 14, 15, 16, 17]. Published studies have mainly reported standard fractionation and hypofractionated brachytherapy regimens in patients treated with HDR-BT, and the biological effective dose (BED) was often calculated due to define the total dose and dose for fractions regimen for a better local control and acceptable late and acute toxicity [19, 20, 21, 22, 23, 24, 25, 26, 33, 34, 35, 36, 37].…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the other radiotherapy technique, HDR-BT might be a better therapeutic option due to essential advantages such as high radiation dose concentration into the clinical target volumes (CTV), rapid dose fall-off at target periphery, optimal sparing of normal tissues in sensitive structures, shorter treatment time, and the use of hypofractionated course [11, 12, 13, 14, 15, 16, 17]. …”
Section: Purposementioning
confidence: 99%
“…To re-emphasise, brachytherapy techniques seem to be the most effective and easy treatment to protect organs located deeper than 2 cm below the surface, and from the perspective of protecting critical healthy organs as well. However, it demands technical expertise in these cases [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kowalik et al . [ 23 ] described CT based HDR surface mold brachytherapy technique for three unfavorably localized malignant lesion and have described in detail the process of manufacturing individual applicator. Similarly, we in our study used CT based plan optimization.…”
Section: Discussionmentioning
confidence: 99%